Management Skills as Determinant for Selecting Management Model Among Sports Managers in Kwara State, Nigeria - Ibraheem Musa Oluwatoyin; Abdulraheem Yinusa Owolabi; Aina Gbemisola Michael (INDONESIAN JOURNAL OF SPORT MANAGEMENT, 2021)
Knowledge, understanding and displaying good management skills will help sports managers of the sports organization to position the teams and clubs. Descriptive correlation study carried out using a survey method for this study. Purposive sampling technique was used to select 85 sports managers of the sports organization. Data were collected using self-developed questionnaire as an instrument. The entire questionnaire yielded a reliability value of 0.77r. Data were analysed using multiple linear Regression at the 0.05 alpha levels.The findings show significant multiple correlations. The regression indicated that the management skills was a good contributor for the selection of management model (F (4, 95) = 2.267, P ˂ .000). Based on the findings of this study, the researcher concluded that management skills contribute to the selection of the management model. Recomendation on government and stakeholder in the state should organize seminar, workshop and training for sports managers of the sports organizations in Kwara state for them to have knowledge on management skills which is crucial to their job.